Experiences, challenges, and prospects of promoting digital inclusion of the elderly in China - Yifan Yang; Zhiyi Xie; Junhao Pan; Yufan Cheng (Public Administration and Policy)
Purpose – The Fourth Industrial Revolution, driven by the Internet, has formed a new digital social ecology. In the dual context of China’s aging demographic structure and the overarching layout and planning of a digital China, there is an urgent need to review its digital policies in bridging the digital divide for the elderly and to identify lessons to be learnt by other countries. Design/methodology/approach – This paper is based on a real-life case study that condenses China’s policies, deconstructs the causes of the digital divide among the elderly from the perspective of the “Three-Level Digital Divide” model, through a qualitative analysis to examine the implications of China’s digital inclusion strategies. Findings – The Chinese Government has played a leading role in bridging the digital divide for the elderly. A series of measures has been taken, including promoting the equitable distribution of digital infrastructure, strengthening digital education for the elderly, and promoting the age-appropriate transformation of digital devices and services. These policies have achieved positive results. Originality/value – The potential role of new technologies in socioeconomic transformation, exemplified through the case study, should be recognized and replicated. Innovative approaches to protect the digital rights and interests of the elderly and promote equitable development are analyzed through a novel model that dissects the digital divide among the elderly with more sustainable and inclusive solutions.